Factors Associated with Low Birth Weight deliveries in Pumwani Maternity Hospital, Nairobi-Kenya - Kwamboka, Mogire, Grace (My University, 2014)
Low birth weight (LBW) is a major determinant of morbidity, mortality and disability in infancy and childhood and has a long-term impact on health outcomes in adult life. It results in substantial costs to the health sector and imposes a significant burden on society as a whole. This study sought to determine risk factors associated with LBW deliveries in Pumwani Maternity Hospital (PMH), Nairobi, Kenya. It focused on LBW and maternal socio-demographic characteristics, lifestyle and medical factors. This was a cross-sectional study which comprised of 405 women who delivered at Pumwani Maternity Hospital between December 2010 and February 2011. Systematic Random sampling was used to select the study participants. Face to face interviews using semi-structured questionnaires were used for data collection. Data analysis was conducted using SPSS version 16.0. The prevalence of LBW was 32.8%. There was a significant association between LBW and average number of meals consumed per day during pregnancies (OR= 2.65, p=0.001), maternal anaemia (OR= 22.53, p=0.001), hypertension (OR= 7.14, p<0.001), vaginal bleeding (OR 74.50, p<0.001), abdominal pain (OR= 12.73, p<0.001), lower backache (OR=2.92, p=0.005) and pelvic pressure (OR=9.20, p<0.001). Occurrence of LBW was definite (100%) among mothers who suffered pPROM. The prevalence of LBW in PMH (32.8%) was high compared to the previous prevalence rates that have been reported in Kenya. Since most of LBW deliveries in PMH were due to medical factors, it implies that if proper and timely diagnosis as well as treatment is undertaken, the prevalence can be reduced. Therefore, it is important to upscale antenatal clinic services especially on reproductive health education. There is also need to educate pregnant women on signs and symptoms that could predict adverse pregnancy outcomes like vaginal bleeding.